2017
DOI: 10.1080/17843286.2017.1302625
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of acute kidney injury in children, a single center study

Abstract: Pediatric AKI poses a significant problem and strategies aimed at prevention, early detection, treatment, and adequate follow-up are needed. D+HUS is the most common underlying cause and effective surveillance of Enterohemorrhagic E. coli infections in association with additional measures is highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Mean age of AKI presentation in our examination was 6.28 years. It is similar as in Norway 6.0 years, and Belgium 6.1 years, while in Nigeria was 4.8 years ( 14 , 15 , 16 ). For many years the diagnosis and management of AKI was based on the concept of classification to three main categories: prerenal, intrinsic (renal) and postrenal.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Mean age of AKI presentation in our examination was 6.28 years. It is similar as in Norway 6.0 years, and Belgium 6.1 years, while in Nigeria was 4.8 years ( 14 , 15 , 16 ). For many years the diagnosis and management of AKI was based on the concept of classification to three main categories: prerenal, intrinsic (renal) and postrenal.…”
Section: Discussionsupporting
confidence: 72%
“…As in our study, in most studies, the incidence of boys with AKI is higher in relation to girls. So, in one multicentric study in United States of America 56.4% ( 13 ), in Norway 53% ( 14 ), in Belgium 50.8% ( 15 ) and in Nigeria 68.6% were males ( 16 ).…”
Section: Discussionmentioning
confidence: 96%
“…Al-Qatibi et al (25) found that the severity of renal impairment at baseline did not affect the risk of long-term renal impairment. On the other hand, Keenswijk et al reported that being in the 'Failure' group at the time of AKI was significantly associated with CKD in the sixth month after AKI in children (26).…”
Section: Discussionmentioning
confidence: 99%
“…According to the lesion and cause, acute kidney injury can be divided into 3 categories: prerenal, renal, and postrenal, and each has a different etiology and pathophysiology. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%